Пылеподавляющий эффект эфирных масел в воздухе помещений - Козуля, С.В. (Таврический медико-биологический вестник, 2010)
В результаті проведених досліджень встановлена здатність ефірної олії лаванди і композиції ефірних олій «Поліол» знижувати кількість пилу у повітрі виробничих та учбових приміщень. Композиція «Поліол», порівняно з ефірною олією лаванди, викликала більш значне зниження кількості пилу у повітрі. As a result of the conducted researches ability of essential oil of lavender and composition of essential oils of «Poliol» to reduce the amount of dust in mid air production and educational apartments is set. Composition of «Poliol», by comparison to essential oil of lavender, caused more considerable decline of dust-ladenness of air in these apartments.